2017
DOI: 10.1186/s12913-017-2759-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of need for help with weight loss among overweight and obese men and women in the Netherlands: a cross-sectional study

Abstract: BackgroundNeed for help is perceived as an important first step towards weight related health-care use among overweight and obese individuals and several studies have reported gender as an important predisposing characteristic of need for help. Therefore, the goal of the current study is to gain insight into factors that might determine need for help for weight loss in men and women.MethodsIn the current study, data from the Dutch cross-sectional survey Health Monitor 2012 was used. Overweight and obese men (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…This may be due to the fact that those with a higher BMI are likely to have more comorbidities than their lighter counterparts and that the burden of their health conditions motivates their attendance. There is growing evidence that those with comorbidities are more likely to seek help or to continue engaging with services if they perceive their health as poor . This would suggest that the presence of comorbidities alone is not necessarily a predictor of attendance and that the perceived impact of comorbid conditions is a driving force behind initial attendance and ongoing engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the fact that those with a higher BMI are likely to have more comorbidities than their lighter counterparts and that the burden of their health conditions motivates their attendance. There is growing evidence that those with comorbidities are more likely to seek help or to continue engaging with services if they perceive their health as poor . This would suggest that the presence of comorbidities alone is not necessarily a predictor of attendance and that the perceived impact of comorbid conditions is a driving force behind initial attendance and ongoing engagement.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that those with comorbidities are more likely to seek help or to continue engaging with services if they perceive their health as poor. 19,20 This would suggest that the presence of comorbidities alone is not necessarily a predictor of attendance and that the perceived impact of comorbid conditions is a driving force behind initial attendance and ongoing engagement.…”
Section: Baseline Characteristics and Attendancementioning
confidence: 99%
“…For the majority of participants, fear resulted from a medical consultation or medical consequences, which motivated them to engage in weight loss services. This is reflected in the literature; help seeking for weight loss [37] and higher uptake of weight loss services [21] is observed in men when a medical comorbidity exists, when a man is referred by their GP [7] or when a man perceives that his health is at risk [38]. Other qualitative research with men has also found that receiving information about their health risk status and weight motivated men to engage with a programme [39].…”
Section: Discussionmentioning
confidence: 99%
“…For the majority of participants, fear resulted from a medical consultation or medical consequences, which motivated them to engage in weight loss services. This is reflected in the literature; help seeking for weight loss [37] and higher uptake of weight loss services [21] is observed in men when a medical comorbidity exists, when a man is referred by their GP [7] or when a man perceives that their health is at risk [38]. Other qualitative research with men has also found that receiving information about their health risk status and weight motivated men to engage with a programme [39].…”
Section: Discussionmentioning
confidence: 99%
“…They felt that worrying about weight was a 'woman's thing', and that being seen to be concerned or talk about dieting challenged their selfidentity and masculinity. Other studies have also reported on the incompatibility of the construct of masculinity with weight loss in men [37,38]. For example, contemporary social norms about body size for men dictate that the ideal body size is big and strong [38] and taking part in 'feminine'…”
Section: Discussionmentioning
confidence: 99%